Pengelolaan Sampah Anorganik Menjadi Nilai Rupiah Pada Generasi Muda Di Desa Jungutbatu - Dewi, Ni Putu Mega Yunita Kristina; Pradhana, I Putu Dharmawan (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Garbage is a serious problem. From the presence of human activities plus an increase in population and economic growth, the volume of waste generation will also increase. If the waste is left unchecked, it will cause pollution to the environment. Jungutbatu Village, which is not free from problems in environmental cleanliness, especially ineffective waste management, so that the waste management carried out is from community garbage collection and public places that are collected and then transported by garbage car and immediately taken to the final disposal site (TPA). Conditions like this will worsen if the management is still ineffective and efficient and not well coordinated. Therefore, the method of activities carried out is observation and socialization. This socialization was carried out in order to educate the younger generation about the management and utilization of waste, especially inorganic waste which can be recycled and can even generate rupiah value. So that the understanding of waste management can increase, starting with the sorting and management of waste and the younger generation and the community are more aware of the importance of waste management and maintaining a clean environment. Keywords: Inorganic Waste, Waste Management, Waste Utilization